Estudo da fisiologia do crescimento, produção de biomoléculas e fotossíntese em 30 espécies de microalgas verdes de água doce - Camargo, Eduardo Caffagni de (Universidade Federal de São Carlos, 2020)
Studies on the physiology and photosynthesis of microalgae are an essential contribution to projects aimed at carbon fixation and biomass production for commercial purposes. Green microalgae (Chlorophyta stricto sensu) comprise a vast diversity of species, yet few of them have been massively cultured. The present research aimed at screening 30 species of Chlorophyta for their growth, photochemical performance, primary production and ability to accumulate biomolecules (chlorophyll, carotenoids, proteins and carbohydrates). All cultures were kept under controlled laboratory conditions. The results showed that Chlorella sorokiniana stood out in virtually every analyzed aspect. Muriella decolor presented a significant growth rate and cell density. The accumulation of total carotenoids was substantial in Monoraphidium griffithii, Chlorolobion braunii and Curvastrum pantanale. New information was found regarding protein productivity in Hariotina reticulata and Chlorolobion lunulatum. C. lunulatum, C. pantanale, H. reticulata, Scenedesmus quadricauda and Desmodesmus spinosus are potential carbohydrate producers. The evaluation of different photochemical parameters and the estimation of the microalgae’s gross primary production (PB) were carried out through Pulse-Amplitude-Modulation (PAM) fluorometry, the main assessment tool applied in this research. C. sorokiniana, D. spinosus and D. communis stood out in terms of PB. As a consequence, they are potential organisms for carbon mitigation. Inferring PB based only on the algae’s specific growth rate, as we initially hypothesized, was found not to be possible, since both variables are moderately correlated. Nonetheless, a strong correlation between PB (under in vivo conditions) and total carbohydrate productivity was observed. Using in vivo samples was considered a more appropriate way of quantifying PB rather than adding a chlorophyll-a extraction step to the same method, since it affects the samples integrity, thus compromising the interpretation of physiological data. This study thereby provides a solid basis for researchers interested in carbon mitigation and potential biotechnological applications involving the 30 strains investigated.
Growth, production of biomolecules and photosynthesis in 30 species of freshwater green microalgae: a physiological study
Keywords: Bioprospecção; Biotecnologia; Fluorescência; Bioprospection; Biotechnology; Fluorescence; Chlorophyta; CIENCIAS BIOLOGICAS::BOTANICA::BOTANICA APLICADA; CIENCIAS BIOLOGICAS::BOTANICA::FISIOLOGIA VEGETAL; CIENCIAS BIOLOGICAS::BOTANICA; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::BIOLOGIA E FISIOLOGIA DOS MICROORGANISMOS; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA